Changes in habitat utilization of slope-spawning flatfish across a bathymetric gradient. (22nd July 2016) - Vestfals, Cathleen D.; Ciannelli, Lorenzo; Hoff, Gerald R.
Abstract: Understanding how fish distributions may change in response to environmental variability is important for effective management of fish populations, as predicted climate change will likely alter their habitat use and population dynamics. This research focused on two commercially- and ecologically-important flatfish species in the eastern Bering Sea (EBS), Greenland halibut ( Reinhardtius hippoglossoides ) and Pacific halibut ( Hippoglossus stenolepis ), which may be especially sensitive to climate-induced shifts in habitat due to strong seasonally and ontogenetically variable distributions. We analysed data from fishery-dependent and fishery-independent sources to determine how environmental variability influenced habitat use, thus gaining a uniquely comprehensive range of seasonal and geographic coverage of each species' distribution. Greenland and Pacific halibut exhibited strong and contrasting responses to changes in temperature on the shelf, with catches decreasing and increasing, respectively, beyond 1 °C. The effect of temperature was not as prominent along the slope, suggesting that slope habitats may provide some insulation from shelf-associated environmental variability, particularly for Greenland halibut. With warming, Greenland halibut exhibited more of a bathymetric shift in distribution, while the shift was more latitudinal for Pacific halibut. Our results suggest that habitat partitioning may, in part, explain differences in Greenland and Pacific halibut distributions. This research adds to our understanding of how the distributions of two fish species at opposite extremes of their ranges in the EBS – Greenland halibut at the southernmost edge and Pacific halibut at the northernmost edge – may shift in relation to a changing ocean environment.